Testing strength of biotic resistance against an introduced fish: inter-specific competition or predation through facultative piscivory? - J Robert Britton (Public Library of Science (PLoS), 2012)
Biotic resistance is the process where aspects of the receiving environment inhibit the establishment and invasion of an introduced species. Resistance against an introduced fish can be through strong competition and/or predation from resident fishes. Here, the biotic resistance against introduced topmouth gudgeon Pseudorasbora parva (a highly invasive fish in Europe) by resident carp Cyprinus carpio was tested in experimental mesocosms. The introduction scenario was six adult P. parva (three male, three female) on a single occasion. Resistance to their establishment was provided by three and six resident C. carpio whose effects on P. parva growth and reproduction were compared to a Control (no resident fish at the time of introduction) and treatments containing three and six P. parva. After 120 days, the growth rates of the introduced P. parva were significantly depressed in C. carpio presence and in mesocosms with three C. carpio present, significantly decreased numbers of 0+P. parva were recorded. Where six C. carpio were present, no 0+P. parva were recorded, indicating resistance strength increased with carp abundance. In contrast, there were no differences in P. parva reproduction and growth rates between the Control and treatments containing conspecifics. Stable isotope analysis (δ(15)N, δ(13)C) revealed C. carpio were feeding at one trophic level above 0+P. parva, suggesting the process of resistance was predation (facultative piscivory) rather than competition. Thus, if P. parva are to establish and invade following an introduction, they must overcome this biotic resistance from cyprinid fishes such as C. carpio.